Selection of Excipients for Haloperidol Formulation for Nose-to-Brain Delivery: A Drug-Excipient Compatibility Study - Kumar Singh, Parvansh; Naseer, Md Arif; Mohamed, Jamal Moideen Muthu; Thankakan Vimala, Ajay Kumar (Journal of Neonatal Surgery, 2025)
Objective: The current research was designed to assess the physical compatibility of short-listed pharmaceutical excipients with micronized haloperidol as a requirement for nasal formulation from nose-to-brain targeting point of view to the neonates. Physical and chemical stability of drug-excipient blends is principal in formulating safe and effective intranasal products. Methods: Haloperidol-excipient binary combinations and some single excipients were kept in white and amber glass containers in a stable condition. Their physical state was monitored for the first time and at the end of 1, 3, and 6 months to test for any evidence of incompatibility like color change, precipitation, or phase separation. Poloxamer 407, benzalkonium chloride solution (50%), polysorbate 80, disodium edetate (dihydrate), microcrystalline cellulose and carboxymethyl cellulose (Avicel cl-611), and glycerol are some tested excipients. Results: The entire excipients and their individual combinations with haloperidol were physically stable for the six months. No color, clarity, or consistency shift was detected in any of the mixtures or pure ingredients under either of the two storage conditions (amber or white glass vials). Combinations of haloperidol with disodium edetate (dihydrate), poloxamer 407, and Avicel CL-611 showed no change from their original white to off-white appearance, thus showing no detectable physical incompatibility. Conclusion: Physical stability of the excipients investigated with micronized haloperidol was good and therefore were suitable candidates to be utilized for follow-up formulation development of a nasal formulation for nose-to-brain targeting. These results warrant the use of these excipients in preformulation screening and stability testing in preparation of an optimal intranasal delivery system for central nervous system targeting.